Gestión administrativa del Quevedo shopping center y su relación con la rentabilidad, cantón Quevedo, año 2013 - Vasco Morán, Jessica Lorena (2015)
The Municipal Government of Quevedo considering promoting the welfare of its inhabitants agreed to the creation of the Administrative Unit Quevedo Shopping Center in July 2009, considered this project as an opportunity to offer merchants a decent, attractive place that captures the attention of visitors. During these six years that has kept the project have been multiple disadvantages that have arisen and which has caused unrest among people from Quevedo and the same traders who occupy the mall, which is considered as a project not attractive. Many of those involved believe that the problems generated by poor management by the management of the institution, which takes minimal effort to change their situation and really potentiate this work, which was intended as a tourist tractive de Quevedo and a place of ongoing visit of the quevedeños. This research raised primarily to assess the administrative management of Quevedo Shopping Center, located in the city of Quevedo during 2013, for which the duties and authorities of the CEO by an evaluation by the board of QSC was analyzed. The profitability of the administrative unit was determined considering the income and expenses of the year 2013, as detailed in the income statement. Through the survey to the merchandisers the actions taken by management during 2013 were systematized, further comprising information provided by the two persons who held the post of manager during this period, which was determined by the phases of the process does not apply administrative, and that the assessment of administrative management helps improve the administrative efficiency of Quevedo Shopping Center.